Feedback in Music Performance Teaching - McPherson, Gary E.; Blackwell, Jennifer; Hattie, John (Frontiers in Psychology, 2022)
The purpose of this article is to provide one prominent perspective from the research literature on a conception of feedback in educational psychology as proposed by John Hattie and colleagues, and to then adapt these concepts to develop a framework that can be applied in music teaching. The article confronts what we see as a lack of understanding about the importance of this topic in music education and provides suggestions that will help music teachers refocus how they use feedback within their teaching. Throughout the article, we draw heavily on the work of John Hattie and his colleagues whose explanations on all facets of feedback—but especially those forms of feedback that are focused on ensuring students understand ‘where to next’—have had a huge impact on school education.